Legal Accountability of a Sole Director in Micro and Small Limited Liability Company - Indra Bambang; I Nyoman Sujana; Putu Ayu Sriasih Wesna (Journal Research of Social Science, Economics, and Management, 2022)
There is a need to investigate the regulation of legal accountability of a Sole Director who is also the founder of the company in a micro and small Limited Liability company based on Article 153 letter J of the Job Creation Law, because of the possibility of an ill-intentioned Director trying to protect his/her personal assets and assuming liability only for the shares he owns. Based on the aforementioned background, the problems in this study can be formulated as follow: 1. How is the accountability of a Sole Directors in a micro or small Limited Liability company regulated? and 2. What is the form of legal accountability for the sole Director in a micro and small Limited Liability company? The type of legal research used in this study is normative juridical research. The form of legal liability of a Sole Director in a micro or small Limited Liability company is closely linked to the principle of limited liability of the Board of Directors. If the requirement of having 2 (two) persons is not met, it will result in the limited accountability of the Limited Liability company becoming unlimited accountability. Unlimited accountability means that all legal actions and losses of the Limited Liability company become the personal liability of the founder or shareholder.